KEBIJAKAN ASEAN SENIOR OFFICIALS ON DRUGS MATTERS (ASOD) MENANGGULANGI DRUGS TRAFFICKING DI INDONESIA (2009-2013) - Rahmadhani, Hardi; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research explains about how the ASOD's role of international organizations inaddressing Drugs Trafficking in Indonesian (2009-2013). Indonesian is a country that isbecoming one of the world's gateway Drugs Trafficking in Southeast Asia This research usespluralism approach which this approach has assumption that actor in international relation isn'tjust a state but there‟s another actor one of international organization. In this research, writeruses role theory, sekuritisasi theory, and international organization theory which eachorganization has their duty. ASOD international organization founded in 1984 and has offices innearly every ASEAN member countries, ASOD have a role in establishing external cooperationboth bilaterally and regionally within the framework of the ASEAN member countries, NGOs,and other relevant organizations. to approve a new program in achieving a regional ASEANdrugs free 2015.Keywords : ASOD, ASEAN Drugs Free 2015, Drugs Trafficking, Indonesian